2015
DOI: 10.1002/2015wr016884
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic control of dissolved organic matter concentration and quality in a semiarid artificially drained agricultural catchment

Abstract: Agricultural practices have altered watershed-scale dissolved organic matter (DOM) dynamics, including in-stream concentration, biodegradability, and total catchment export. However, mechanisms responsible for these changes are not clear, and field-scale processes are rarely directly linked to the magnitude and quality of DOM that is transported to surface water. In a small (12 ha) agricultural catchment in eastern Washington State, we tested the hypothesis that hydrologic connectivity in a catchment is the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 108 publications
(170 reference statements)
1
9
1
Order By: Relevance
“…The mean of the yearly artificial drain NO 3 − fluxes (Figure ) was 15 kg N ha −1 year −1 (Table ). Bellmore, Harrison, Needoba, Brooks, and Keller () estimated dissolved organic N (DON) fluxes from the AD over the same interval as this research and reported a mean yearly value of 1.3 kg N ha −1 year −1 .…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The mean of the yearly artificial drain NO 3 − fluxes (Figure ) was 15 kg N ha −1 year −1 (Table ). Bellmore, Harrison, Needoba, Brooks, and Keller () estimated dissolved organic N (DON) fluxes from the AD over the same interval as this research and reported a mean yearly value of 1.3 kg N ha −1 year −1 .…”
Section: Resultsmentioning
confidence: 66%
“…Regarding chemostatic behavior of N reservoirs in agroecosystem catchments, our temporally detailed data show that within each WY, N concentrations are much larger during wintertime peak flows than earlier and later (Figure ). Bellmore et al () observed similar concentration–efflux behavior for AD DON. Thus, at the CAF, both NO 3 − and DON behave chemostatically interannually but not seasonally, implying limited reservoir size and/or availability for export on the seasonal timescale.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Processes impacting stream water DOM characteristics are varied and complex, and despite the fact that our observed relationships between atmospheric S and N deposition, Ca and Mg concentrations, and DOM quantity and quality are consistent with previous studies linking DOM response to atmospheric deposition and divalent cation concentrations (Figure ), we acknowledge that other processes play a role. For example, time‐variable streamflow has been shown to influence DOM quantity and quality [ Hood et al ., ; Inamdar and Mitchell , ; Sebestyen et al ., ; Perdrial et al ., ; Bellmore et al ., ]. While the effects of hydrology on stream water quality cannot be ruled out, many of the effects of time‐variable discharge on stream water quality were accounted for by collecting samples during nonstormflow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The decline in DRP concentration over the water year could either be the result of the depletion of P pools, and/or the increasing contribution of P‐depleted areas to the drain line discharge (Reid et al., 2012). The DRP response during individual storm events exhibited a similar flushing behavior to nitrate and dissolved organic carbon (Bellmore et al., 2015; Kelley et al., 2017), presumably because enriched near‐surface soils contributed preferentially to DRP leaching during those periods (Christianson et al., 2016; King et al., 2015).…”
Section: Discussionmentioning
confidence: 92%